Safety and utility of kidney biopsy in patients with estimated glomerular filtration rate < 30 ml/min/1.73 m(2) - Asad, Riyaz Ahmed (Nephrology (Carlton), 2021)
AIM: Kidney biopsy (KBx) is the gold standard for evaluation of kidney disease, but is associated with a higher risk of complications in patients with reduced glomerular filtration rate (GFR). We studied the safety and utility of KBx in patients with eGFR <30 ml/min/1.73 m(2). METHODS: Consecutive adult patients with eGFR <30 ml/min/1.73 m(2), who were planned for a KBx and consented to participate were prospectively enrolled. Patients with solitary/transplant kidney or acute kidney injury were excluded. Haemoglobin was checked on the day of KBx and repeated 18–24 h later along with a screening ultrasound. Post-KBx complications were noted and their risk-factors analysed. The utility of the KBx was graded as effecting significant, some, or no change to subsequent management. RESULTS: Of the 126 patients included, 75% were male, 27.7% were diabetic, and the median eGFR was 13.5 ml/min/1.73m(2). Major complications occurred in 5.6%. Perirenal haematomas were detected in 37.3%, and haematomas ≥2 cm were significantly more frequent in those with eGFR <15 ml/min/1.73 m(2) (29.2% vs. 13%, p = .032). Dialysis was a risk factor, while pre KBx blood transfusion, diabetes and higher serum albumin were protective against any complication. KBx was more likely to make a significant difference in management in those with eGFR 15–29 ml/min/1.73m(2) (44.1% vs. 11.1%, p < .001). Increasing age, lower serum creatinine and albumin were independently associated with KBx utility. CONCLUSION: KBx is relatively safe in severe kidney disease but its risk to benefit balance needs to be carefully considered when eGFR is <15 ml/min/1.73m(2).